2017
DOI: 10.17222/mit.2015.185
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chemical additives and curing conditions on the mechanical properties and carbonation resistance of alkali-activated slag composites

Abstract: The main aim of the presented work is to investigate the effect of the addition of air-entraining (AEA) and shrinkage-reducing agents (SRA) on the mechanical properties and carbonation resistance of alkali-activated slag (AAS). The materials used for the sample preparation were blast-furnace slag activated using sodium silicate and AEA or SRA in various amounts. The samples were cured in various conditions (air curing under laboratory conditions and water curing at the same temperature) and the influence of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The coarser pore structure of SRA1.0 specimens compared to those without SRA led to a modified weight loss development, with accelerated weight loss rate during the first days of drying. A slight increase in weight beyond the third day of dry air exposure is probably caused by the intense carbonation which was, together with the relatively low strengths of these air-stored specimens, presented in [ 53 ]. The importance of the pore size distribution for drying shrinkage was emphasized by Collins and Sanjayan [ 18 ] and it can thus be concluded that the great reduction of drying shrinkage induced by 1% of SRA is attributed to coarser pores, where the shrinkage forces are not so high.…”
Section: Resultsmentioning
confidence: 99%
“…The coarser pore structure of SRA1.0 specimens compared to those without SRA led to a modified weight loss development, with accelerated weight loss rate during the first days of drying. A slight increase in weight beyond the third day of dry air exposure is probably caused by the intense carbonation which was, together with the relatively low strengths of these air-stored specimens, presented in [ 53 ]. The importance of the pore size distribution for drying shrinkage was emphasized by Collins and Sanjayan [ 18 ] and it can thus be concluded that the great reduction of drying shrinkage induced by 1% of SRA is attributed to coarser pores, where the shrinkage forces are not so high.…”
Section: Resultsmentioning
confidence: 99%